The (re) urbanization of Honolulu: colonialism and urban renewal in Hawai’i - Charles, Shea (2021)
In this essay, I explore the implications of (neo)colonialism on Ke’eaumoku street and look towards indigenous and community-based answers. As issues of gentrification, homelessness, and the rising cost of living plague Hawai’i, many look for ways to solve these issues as an “Us” (Hawai’i Residents) versus “Them” (Continental U.S. and International Corporations) dichotomy, as opposed to looking towards the broader issues of colonialism and the further implications. To do this, I specifically look at the Transit-Oriented Development and make connections between the historical and contemporary urbanization of Honolulu and the ongoing colonization of Hawai’i. I also suggest that the social action previously taken by communities in Kaka’ako should be used for the Ke’eaumoku street community.